2006
DOI: 10.1300/j013v42n02_03
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence: A Tragedy Behind the Doors

Abstract: Placing more importance on educating girls could be a key component of preventing domestic violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Another finding of the study was that husbands' witnessing violence to their mothers by their fathers during their childhood affected the physical and psychological violence against women positively and significantly. Ergin, Bayram, Alper, Selimoğlu and Bilgel (2005) investigated the prevalence, frequency, types and reasons of marital violence against woman in a metropolitan city of Turkey (Bursa). The empirical applications were based on horizontal cross-sectional data in 2003.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another finding of the study was that husbands' witnessing violence to their mothers by their fathers during their childhood affected the physical and psychological violence against women positively and significantly. Ergin, Bayram, Alper, Selimoğlu and Bilgel (2005) investigated the prevalence, frequency, types and reasons of marital violence against woman in a metropolitan city of Turkey (Bursa). The empirical applications were based on horizontal cross-sectional data in 2003.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although some studies reported domestic violence regardless of culture, geographical location, economic development, and educational level (Korur, 2003;Ludermir, Lewis, Valongueiro, Barreto, & Araya, 2010;Yanıkkerem, Karadaş, Adigüzel, & Sevil, 2006;Yurdakul, 1996), many others found financial problems as the most important reason for domestic violence (Abasiubong et al, 2010;Altınay, & Arat, 2008;Ergin, Bayram, Alper, Selimoğlu, & Bilgel, 2005;Jewkes, Levin, & Penn, 2002;Kocacık, & Doğan, 2006;Mayda, & Akkuş, 2004;Muhajarine, & D'Arcy, 1999;Okyay et al, 2009;Tokdemir, Deveci, & Acık, 2003;Yanıkkerem et al, 2006). Violence against women is an important social problem in Turkey as well.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, evidence suggests that status and power discrepancies in owning resources and lack of education may be associated with increased domestic violence especially by men who hold traditional ideas about gender and believe that men should be the primary bread-winners for a family (Atkinson, Greenstein, & Lang, 2005). A dearth of literature repeatedly found educational attainment and higher social status as major factors to reduce the likelihood of experiencing domestic violence in developed as well as developing countries (Ergin, Bayram, Alper, Selimoglu, & Bilgel, 2008;Erten & Keskin, 2018;Firestone, Harris, & Vega, 2003;Simister & Makowiec, 2008). The present study in concordance with this found that higher education and upper social class in the Indian caste hierarchy of married adolescent girls were protective factors against partner violence.…”
Section: Discussionmentioning
confidence: 99%